Engaging Students with Mathematics Through Story: A Case of Grade II Children - Singh, Pooja Keshavan; Gandhi, Haneet (Voices of Teachers and Teacher Educators, 2019)
The study discusses how a story acted as a catalyst for engaging primary school learners with mathematics as they learned the concept of repeating pattern. Engagement is viewed as a multidimensional construct made up of cognitive, motivational and emotional aspects occurring together. The study took place with 22 Grade II students (8 boys and 14 girls, age group 7 to 8 years) studying in a Government school of Delhi. The teacher in the study was a pre-service primary grade teacher and the study took place during her internship period. Data analysis showed the coexistence of the three aspects of engagement in the mathematics classrooms that used storytelling as a pedagogic tool. Students were engaged with the mathematical content as much as with the story. The findings also delve into the reasons behind students engagement with mathematics.